Phylogeny and micro-habitats utilized by lizards determine the composition of their endoparasites in the semiarid Caatinga of Northeast Brazil - Brito, S. V.; Corso, G.; Almeida, A. M.; Ferreira, F. S.; Almeida, W. O.; Anjos, L. A. [UNESP]; Mesquita, D. O.; Vasconcellos, A. (Springer, 2014)
Trophic networks can have architectonic configurations influenced by historical and ecological factors. The objective of this study was to analyze the architecture of networks between lizards, their endoparasites, diet, and micro-habitat, aiming to understand which factors exert an influence on the composition of the species of parasites. All networks showed a compartmentalized pattern. There was a positive relation between diet and the diversity of endoparasites. Our analyses also demonstrated that phylogeny and the use of micro-habitat influenced the composition of species of endoparasites and diet pattern of lizards. The principal factor that explained the modularity of the network was the foraging strategy, with segregation between the "active foragers" and "sit-and-wait" lizards. Our analyses also demonstrated that historical (phylogeny) and ecological factors (use of micro-habitat by the lizards) influenced the composition of parasite communities. These results corroborate other studies with ectoparasites, which indicate phylogeny and micro-habitat as determinants in the composition of parasitic fauna. The influence of phylogeny can be the result of coevolution between parasites and lizards in the Caatinga, and the influence of micro-habitat should be a result of adaptations of species of parasites to occupy the same categories of micro-habitats as hosts, thus favoring contagion.
Keywords: Parasitism; Neotropical region; Semiarid; Trophic networks